Dynamics of parasite clearance in cutaneous leishmaniasis patients treated with miltefosine. - Thomas P C Dorlo; Pieter P A M van Thiel; Gerard J Schoone; Ymkje Stienstra; Michèle van Vugt; Jos H Beijnen; Peter J de Vries (Public Library of Science (PLoS), 2011)
Parasite loads were quantified in repeated skin biopsies from lesions of 2 patients with Old-World cutaneous leishmaniasis (CL) caused by Leishmania major and L. infantum during and after treatment with miltefosine. Miltefosine induced a rapid therapeutic effect on both infections with an initial decline of parasites of ∼1 log/week for the L. major infection. These observations illustrate the usability of quantifying parasite loads in skin lesions as a pharmacodynamic measure and quantitative descriptor of drug effect for CL supporting clinical assessment.